Pengaruh Ukuran Perusahaan, Profitabilitas, dan Ukuran Dewan Pengawas Syariah terhadap Pengungkapan Islamic Social Reporting - Riva Intan Sejati; Fatmi Hadiani; Endang Hatma Juniwati (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research is being to testing the impact of company size, profitability, and the size of the Sharia Supervisory Board (DPS) is to provide Islamic Social Reporting (ISR) disclosure in Indonesian Full-Fledged Islamic Bank for the years 2017 through 2021. Eviews12 is a method that is used for quantitative analyzing regressive data panel. By using purposive sampling method, the sample revealed that 11 Full-Fledged Islamic Bank were registered with OJK. FEM (Fixed Effect Model) is the most suitable estimate for this model. The study’s findings show that ISR disclosure is simultaneously have significant positive effect by the size of the company, profitability, and DPS size. ISR disclosure is partially has a significant positive effect by the size of the company. This study may be used to support the Full-Fledged Islamic Bank theory, which seeks to reduce ISR harm based on company size, profitability, and DPS. Keyword: Company size, profitability, DPS size, ISR